2022
DOI: 10.1016/j.urology.2022.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bladder Ultrasound in Prediction of Resolution of Vesicoureteral Reflux After Endoscopic Subureteral Hyaluronic Acid/Dextranomer (Deflux) Injection

Abstract: BACKGROUND: We evaluated the e cacy of bladder ultrasound to predict resolution of vesicoureteral re ux after subureteral endoscopic Hyaluronic acid/dextranome (De ux) injection. METHODS: Between 2010 and 2018, 120 patients (220 ureters) underwent Subureteral De ux injection for re ux in children. Male/female ratio was 1: 5. All patients had voiding cystourethrography and bladder ultrasound at 3 months and one year after surgery. Outcome analysis included: Success rates and presence/ absence of De ux mount by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Arlen et al also suggested that postoperative VCUG could be safely avoided in the majority of children undergoing endoscopic treatment of primary VUR [23]. Bladder ultrasonography is highly sensitive for detecting Deflux ® implants and can anticipate the resolution of reflux with an accuracy of 88.95% in low-grade VUR and 36.67% in high-grade VUR [24]. Postoperative bladder ultrasonography could be modified as a screening tool in the follow up of patients with a primary low-grade VUR treated by Deflux ® injection, while VCUG could be used for the follow up of high-grade VUR patients [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arlen et al also suggested that postoperative VCUG could be safely avoided in the majority of children undergoing endoscopic treatment of primary VUR [23]. Bladder ultrasonography is highly sensitive for detecting Deflux ® implants and can anticipate the resolution of reflux with an accuracy of 88.95% in low-grade VUR and 36.67% in high-grade VUR [24]. Postoperative bladder ultrasonography could be modified as a screening tool in the follow up of patients with a primary low-grade VUR treated by Deflux ® injection, while VCUG could be used for the follow up of high-grade VUR patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Bladder ultrasonography is highly sensitive for detecting Deflux ® implants and can anticipate the resolution of reflux with an accuracy of 88.95% in low-grade VUR and 36.67% in high-grade VUR [24]. Postoperative bladder ultrasonography could be modified as a screening tool in the follow up of patients with a primary low-grade VUR treated by Deflux ® injection, while VCUG could be used for the follow up of high-grade VUR patients [24]. In our setting, we used a radionuclide cystogram to follow the resolution of vesicoureteral reflux in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…The type of surgery was chosen according to the renal function, laterality, and grade of VUR. Surgical options included extravesical ureteral reimplantation for high-grade reflux (grade IV–V) and endoscopic subureteral hyaluronic acid/dextranome (deflux) injection for low-grade reflux (grade I–III) as a double HIT technique [ 11 ]. Grade I is injected when there is a deterioration of reflux with an increasing grade of hydronephrosis.…”
Section: Methodsmentioning
confidence: 99%